Experimental Investigation of Atomizing Performance of Low Pressure Swirl Nozzle. (9th January 2014) - Yan, Yunfei; Zhang, Li; Pan, WenLi; Pu, Ge
Abstract : The lime slurry nozzle is a key equipment component in the flue gas drying desulfurization system. The atomizing performance of lime slurry nozzles with different structure parameters under low pressure conditions was experimentally studied by using the laser diffraction/scattering particle size distribution analyzer (Win212-2), and the optimized structure of nozzle was obtained. Experimental results indicate that there is a relation between the average granularity and the fluid pressure and that the spray angle increases with increasing pressure. As the solid percentage of lime slurry increases, the Sauter Mean Diameter (SMD) of droplets also increases, the atomizing performance of the nozzle slightly decreases, and the spray angle of nozzle also decreases. The flux of lime slurry is uniformly distributed along the radial direction of the nozzle, and then the flux characteristic of the spray nozzle is obtained. In order to meet the size of droplets for the semidry desulphurization process, the performance of an optimum nozzle was experimentally tested. The proper nozzle type and optimal parameters for low pressure swirl nozzles are suggested.